Phosphasalen Indium Complexes Showing High Rates and Isoselectivities in rac‐Lactide Polymerizations. (5th April 2017) - Myers, Dominic; White, Andrew J. P.; Forsyth, Craig M.; Bown, Mark; Williams, Charlotte K.
Abstract: Polylactide (PLA) is the leading bioderived polymer produced commercially by the metal‐catalyzed ring‐opening polymerization of lactide. Control over tacticity to produce stereoblock PLA, from rac ‐lactide improves thermal properties but is an outstanding challenge. Here, phosphasalen indium catalysts feature high rates (30±3 m −1 min −1, THF, 298 K), high control, low loadings (0.2 mol %), and isoselectivity ( P i =0.92, THF, 258 K). Furthermore, the phosphasalen indium catalysts do not require any chiral additives.